2006
DOI: 10.1091/mbc.e05-08-0763
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Phosphate Indirectly Activates KCa3.1 via 14 Amino Acids in the Carboxy Terminus of KCa3.1

Abstract: KCa3.1 is an intermediate conductance Ca2؉ -activated K ؉ channel that is expressed predominantly in hematopoietic cells, smooth muscle cells, and epithelia where it functions to regulate membrane potential, Ca 2؉ influx, cell volume, and chloride secretion. We recently found that the KCa3.1 channel also specifically requires phosphatidylinositol-3 phosphate [PI(3)P] for channel activity and is inhibited by myotubularin-related protein 6 (MTMR6), a PI(3)P phosphatase. We now show that PI(3)P indirectly activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 32 publications
(48 reference statements)
2
59
0
Order By: Relevance
“…For instance, mice deficient for mitsugumin-29 display similar ultrastructural abnormalities, but only minor defects in muscle strength (37). Myotubularin activity on PI(3)P and/or PI(3,5)P 2 could also play a direct role on channel activation, as previously reported for a homologous protein, MTMR6, which regulates the activity of the Ca 2ϩ -activated K ϩ channel KCa3.1 via PI(3)P (38,39). Other mutant mice with deletions in genes involved in triad formation and/or calcium homeostasis, such as junctophilin 1 and triadin, also contain muscles with abnormally oriented T-tubules and alterations in Ca 2ϩ transients and/or E-C coupling (40) (41).…”
Section: Discussionmentioning
confidence: 69%
“…For instance, mice deficient for mitsugumin-29 display similar ultrastructural abnormalities, but only minor defects in muscle strength (37). Myotubularin activity on PI(3)P and/or PI(3,5)P 2 could also play a direct role on channel activation, as previously reported for a homologous protein, MTMR6, which regulates the activity of the Ca 2ϩ -activated K ϩ channel KCa3.1 via PI(3)P (38,39). Other mutant mice with deletions in genes involved in triad formation and/or calcium homeostasis, such as junctophilin 1 and triadin, also contain muscles with abnormally oriented T-tubules and alterations in Ca 2ϩ transients and/or E-C coupling (40) (41).…”
Section: Discussionmentioning
confidence: 69%
“…Together, these findings suggest that macropinocytosis is controlled by the sequential breakdown of PI(3,4,5)P 3 → PI(3,4)P 2 → PI(3)P → PI in the PM. Furthermore, we showed that KCa3.1, a Ca 2+ -activated K + channel that is activated by a PI(3)P (26)(27)(28), is essential for macropinocytosis.…”
Section: Significancementioning
confidence: 98%
“…We recently found that the calcium-activated potassium channel KCa3.1 requires PI(3)P for activity and is specifically inhibited by MTMR6 (21)(22)(23). These studies demonstrated that interaction between the CC domain of MTMR6 with the CC domain in the carboxyl terminus of KCa3.1 is critical for the inhibition of KCa3.1 and proposed that interaction between the CC domains on KCa3.1 and MTMR6 functions to localize MTMR6 at the PM where it then dephosphorylate PI(3)P leading to KCa3.1 inhibition.…”
mentioning
confidence: 99%